CHALLENGING PATRIARCHY IN PARADISE: MARK TWAIN'S PROGRESSIVE GENDER PORTRAYAL IN 'DIARIES OF ADAM AND EVE’ - Ali, Muhammad Ilham (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2024)
Despite extensive research on Mark Twain's works, few studies have examined his portrayal of gender roles in "Diaries of Adam and Eve" through a feminist lens. This study aims to fill this gap by analyzing Twain's representation of Eve and Adam, exploring how his writing both reflects and challenges societal beliefs centered around male power and control. The research employs a qualitative methodology, utilizing feminist and gender theory to conduct a close textual analysis of "Diaries of Adam and Eve." The study focuses on language, tone, and themes used in Twain's portrayal of the two characters, contextualizing these elements within the historical and social framework of women's rights in the late 19th and early 20th centuries. Findings reveal a nuanced depiction of gender roles that both conform to and subvert traditional expectations. Eve is portrayed as intelligent, curious, and capable, challenging conventional female stereotypes and reflecting an emerging understanding of women's rights and equality. In contrast, Adam's characterization aligns more closely with traditional notions of male authority and power. The study demonstrates a clash between traditional views on gender roles and modern perspectives on women's rights within Twain's work. It highlights Twain's critical examination of gender issues and his implicit support for women's equality, contributing to our understanding of his progressive stance on gender roles. This research provides valuable insights into Twain's subtle commentary on societal norms and his contribution to early feminist discourse through literature.